2020
DOI: 10.1177/0300060520926025
|View full text |Cite
|
Sign up to set email alerts
|

Management of thoracogastric airway fistula after esophagectomy for esophageal cancer: A systematic literature review

Abstract: Background Thoracogastric airway fistula (TGAF) is a serious complication of esophagectomy for esophageal cancer. We conducted a systematic review of the appropriate therapeutic options for acquired TGAF. Methods We performed a literature search to identify relevant studies from PubMed, EMBASE, and Web of Science using the search terms “gastric airway fistula”, “gastrotracheal fistula”, “gastrobronchial fistula”, “tracheogastric fistula”, “bronchogastric fistula”, “esophageal cancer”, and “esophagectomy”. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…All interventional techniques could prove significantly longer survival compared to best supportive care. A previous study aligns with this finding [ 15 ], while a meta-analysis of 89 S-RDF patients demonstrated longer survival after surgery compared to bronchial stenting [ 32 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…All interventional techniques could prove significantly longer survival compared to best supportive care. A previous study aligns with this finding [ 15 ], while a meta-analysis of 89 S-RDF patients demonstrated longer survival after surgery compared to bronchial stenting [ 32 ].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, no previous study fully addressed anatomical considerations of RDF therapy: whether one or both fistula orifices should be sealed. This has been underlined by several studies, which concluded that the appropriate management of RDF is still uncertain and variable [ 18 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBF might develop either in the early or the late postoperative period after esophagectomy with gastric pull-up, and can occur anywhere in the respiratory tract, from the trachea to the lobar bronchus. The most common clinical signs and symptoms are cough on swallowing, followed by fever, choking, chest pain, dyspnea, pneumonia, and life-threatening hemoptysis; [ 10 ] respiratory failure with septic shock is the most common cause of death. [ 11 ] A thoracic computed tomography scan with contrast, gastroscopy, bronchoscopy, and upper gastrointestinal contrast studies typically confirm GBF presence.…”
Section: Discussionmentioning
confidence: 99%
“…1 The treatment strategy for gastrobronchial fistula is still controversial; however, nonsurgical procedures are preferable because of the invasiveness of surgical procedures. 2 Previously, we performed surgery for similar cases; however, it required the removal of the gastric tube posterior to the sternum, which is extremely invasive. Here, the combination of EWS and the OTSC system was used as a nonsurgical procedure.…”
Section: Discussionmentioning
confidence: 99%